2015
DOI: 10.3340/jkns.2015.57.3.167
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Lumbar Cerebrospinal Fluid Drainage to Reduce the Cerebral Vasospasm after Surgical Clipping for Aneurysmal Subarachnoid Hemorrhage

Abstract: ObjectiveRemoval of blood from subarachnoid space with a lumbar drainage (LD) may decrease development of cerebral vasospasm. We evaluated the effectiveness of a LD for a clinical vasospasm and outcomes after clipping of aneurysmal subarachnoid hemorrhage (SAH).MethodsBetween July 2008 and July 2013, 234 patients were included in this study. The LD group consisted of 126 patients, 108 patients in the non LD group. We investigated outcomes as follow : 1) clinical vasospasm, 2) angioplasty, 3) cerebral infarctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 41 publications
0
32
0
1
Order By: Relevance
“…15,16 Aneurysms located in the basal cisterns, anterior communicating aneurysm, posterior circulation aneurysm, severity of aSAH, higher Fischer grade, use of EVD and non-opening of lamina terminalis are some of the other factors leading to DH in aSAH cases . [9][10][11] Decompressive craniectomy in association with low GCS, CSF infection, higher Fischer grade, advanced age and time of cranioplasty is related with increased chances of DH. The cause of DH may be secondary to CSF fl ow blockage around the convexity.…”
Section: Etiology Of Dhmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Aneurysms located in the basal cisterns, anterior communicating aneurysm, posterior circulation aneurysm, severity of aSAH, higher Fischer grade, use of EVD and non-opening of lamina terminalis are some of the other factors leading to DH in aSAH cases . [9][10][11] Decompressive craniectomy in association with low GCS, CSF infection, higher Fischer grade, advanced age and time of cranioplasty is related with increased chances of DH. The cause of DH may be secondary to CSF fl ow blockage around the convexity.…”
Section: Etiology Of Dhmentioning
confidence: 99%
“…The advantages of LD in these DH cases have been well studied in literature. 2,6,[9][10][11]15,17,[24][25][26][27] In aSAH as shown by the LUMAS study in 2012 there is a reduction of prevalence of delayed ischemic neurological defi cit and improves early clinical outcome. 28 LD has also been shown to be benefi cial in post aneurysm coil embolization associated DH.…”
Section: Management Of Dhmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical and experimental studies have reported that the volume and duration of subarachnoid blood clotting are directly associated with the development and severity of cerebral vasospasm [8,28]. Indeed, the removal of blood clots through irrigation of the subarachnoid space reportedly reduced the risk of cerebral vasospasm [11,14,21]. In addition, as causes of cerebral vasospasm are multifactorial, its preventive treatment would require a combination of approaches, including anti-oxidant and anti-inflammatory reagents, or a reagent with pleiotropic effects.…”
Section: Fax Number: +81-11-706-5278 26mentioning
confidence: 99%
“…These patients also present with disorders of consciousness, facial paralysis, and swallowing disturbance, which are all associated with an increased incidence of pneumonia. Furthermore, 50% of patients with an intracerebral hemorrhage also have respiratory infections [1,2].…”
Section: Introductionmentioning
confidence: 99%